Computational musculoskeletal modeling of compensatory movements in the upper limb. (17th July 2020) - Reilly, Michael; Kontson, Kimberly
Abstract: It is well documented that most upper limb amputees utilize compensatory movement strategies to accomplish everyday tasks when using a prosthetic device and that musculoskeletal complaints (MSCs) are more common in this population. However, little information is available on how the loss of distal degrees of freedom (DOFs) in the arm impact muscle force, thereby limiting our understanding of the mechanism by which these MSCs are manifesting. Knowledge of how a loss of DOFs may lead to MSCs can enable clinicians to provide more targeted guidance on how best to restore functional ability while addressing pain, and may serve as a tool for prescriptive decision-making when determining the impact of device selection on long-term clinical needs. 3D motion capture data were collected from 12 right-handed subjects with no upper limb disability using an 8-camera Vicon™ motion analysis system as they performed the targeted Box and Blocks test under normal and braced conditions to simulate a loss of DOFs in the wrist and fingers. Muscle force data were calculated using AnyBody Modeling Software™ for four different muscles: erector spinae, infraspinatus, deltoid, and trapezius. Linear mixed effects models were generated using the peak force data and mean force data for a given muscle fascicle. The fixed effect coefficient and 95% confidence intervals were reported for each muscle fascicle. Overall, a strong effect of condition on muscle force was seen for most muscles in the right side of the body (specifically deltoid and infraspinatus), with greater forces generated during the braced condition.